2007
DOI: 10.1111/j.1475-4762.2007.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Moralising geographies: stigma, smoking islands and responsible subjects

Abstract: As the long-term negative health effects of continued smoking have become more obvious, smoking cessation has become a key focus of government attention across the developed world. Smoking cessation programmes have had mixed outcomes, with rates of smoking in certain socio-economically disadvantaged and ethnic minority groups remaining high. The increasing stigmatisation of those who continue to smoke, coupled with the spatial segregation of poor and minority populations, may compound to produce 'smoking islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
190
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(201 citation statements)
references
References 50 publications
8
190
0
3
Order By: Relevance
“…That such a higher exposure is in fact correlated with a higher demand is confirmed by several studies on tobacco and alcohol (18,38,39) . Several authors report spatial aggregation structures in the form of so-called 'smoking islands' (40) . According to three current reviews, the majority (23,41,42) but not all (43,44) of the studies also identified a significant association between a healthy community food environment and limited access to fastfood restaurants, on the one hand, and healthy diets and lower obesity rates on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…That such a higher exposure is in fact correlated with a higher demand is confirmed by several studies on tobacco and alcohol (18,38,39) . Several authors report spatial aggregation structures in the form of so-called 'smoking islands' (40) . According to three current reviews, the majority (23,41,42) but not all (43,44) of the studies also identified a significant association between a healthy community food environment and limited access to fastfood restaurants, on the one hand, and healthy diets and lower obesity rates on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…In adopting a grounded theory methodology for the study, I sought to disrupt and challenge the many voices of tobacco control researchers and advocates who continue to maintain strategies of denormalisation, increasing restrictions, and stigmatisation of smoking and smokers despite the implications for Indigenous peoples and other disadvantaged groups (Thompson, Pearce, & Barnett, 2007).…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…More broadly, our analysis builds on existing work to show how denormalisation policies have not only stigmatised the practice of smoking, but have also called smokers' identities (their moral and social worth) into question Greaves et al, 2010;Holdsworth & Robinson, 2008;Thompson et al, 2007;Wigginton & Lafrance, 2015). This raises questions about the extent to which stigmatisation serves to construct certain 'profiles' of moral and healthy citizens -thus moving beyond a targeting of behaviour to a targeting of groups of people.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence documenting smokers' experiences of stigmatisation in light of tobacco denormalisation policies Burgess et al, 2009;Greaves, Oliffe, Ponic, Kelly, & Bottorff, 2010;Kim & Shanahan, 2003;Phillips, Amos, Ritchie, Cunningham-Burley, & Martin, 2007;Ritchie, Amos, & Martin, 2010;Thompson et al, 2007;Wigginton & Lee, 2013). For example, the authors of an analysis of interviews with 40 Scottish smokers argued that since the introduction of smoke-free legislation, smokers had experienced a loss of social status in public spaces.…”
Section: Smoking-related Stigmamentioning
confidence: 99%
See 1 more Smart Citation